2022
DOI: 10.3390/en15197190
|View full text |Cite
|
Sign up to set email alerts
|

Progress on Conventional and Advanced Techniques of In Situ Transesterification of Microalgae Lipids for Biodiesel Production

Abstract: Global warming and the depletion of fossil fuels have spurred many efforts in the quest for finding renewable, alternative sources of fuels, such as biodiesel. Due to its auxiliary functions in areas such as carbon dioxide sequestration and wastewater treatment, the potential of microalgae as a feedstock for biodiesel production has attracted a lot of attention from researchers all over the world. Major improvements have been made from the upstream to the downstream aspects related to microalgae processing. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 224 publications
0
3
0
Order By: Relevance
“…However, the high heating value of all biodiesel was slightly lower than that of WCO biodiesel [38]. As a result, the high heating value of biodiesel is usually lower than that of conventional diesel, leading to a slight reduction in engine power and torque of 7% and 8%, respectively [27]. The current results of biodiesel which has a high heating value (HHV) correspond with previous studies.…”
Section: Heating Valuesupporting
confidence: 84%
See 1 more Smart Citation
“…However, the high heating value of all biodiesel was slightly lower than that of WCO biodiesel [38]. As a result, the high heating value of biodiesel is usually lower than that of conventional diesel, leading to a slight reduction in engine power and torque of 7% and 8%, respectively [27]. The current results of biodiesel which has a high heating value (HHV) correspond with previous studies.…”
Section: Heating Valuesupporting
confidence: 84%
“…The second generation includes biodiesel from waste cooking oil [7,26]. Nowadays, various studies worldwide are investigating biodiesel production from microalgae, which is considered the third generation [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Another challenge faced by LCA is that a majority of studies are based on theoretical analyses, which may not necessarily align with practical applications [75]. This issue is particularly evident in the field of microalgae-to-bioenergy technologies, where data from large-scale plants are currently either unavailable or insufficient [76,77]. As a result, researchers often rely on mathematical models, such as simulations and optimization procedures, to conduct scale-up studies [77].…”
Section: Challenges Of Lcamentioning
confidence: 99%
“…This issue is particularly evident in the field of microalgae-to-bioenergy technologies, where data from large-scale plants are currently either unavailable or insufficient [76,77]. As a result, researchers often rely on mathematical models, such as simulations and optimization procedures, to conduct scale-up studies [77]. In such cases, the researchers have to rely on data obtained from laboratory-scale studies, which can introduce inaccuracies in the presented data.…”
Section: Challenges Of Lcamentioning
confidence: 99%
“…However, a detailed comparison between d‐trans and ext‐trans using microalgae has not been elucidated. Besides the latest work of Makareviciene & Skorupskaite 19 and Ideris et al ., 20 who reviewed ext‐trans and d‐trans for biodiesel production from microalgae, not much work has been reported regarding this comparison method. Therefore, the study reported here examined the production of FAMEs from Chlorella vulgaris using d‐trans and ext‐trans.…”
Section: Introductionmentioning
confidence: 99%